2021
DOI: 10.1086/713903
|View full text |Cite
|
Sign up to set email alerts
|

How Dissent on Gender Bias in Academia Affects Science and Society: Learning from the Case of Climate Change Denial

Abstract: Gender bias is a recalcitrant problem in academia and society. However, dissent has been created on this issue. We focus on dissenting studies by Stephen J. Ceci and Wendy M. Williams, arguing that they reach conclusions that are unwarranted on the basis of the available evidence and that they ignore fundamental objections to their methodological decisions. Drawing on discussions from other contexts, particularly on manufactured dissent concerning anthropogenic climate change, we conclude that dissent on gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In sum, conditions 1 and 2 of the IndRA hold for the given case, but conditions 3 and 4 only partially. This indicates that the case differs from cases of epistemically detrimental dissent we have investigated more recently, such as denial of anthropogenic climate change (Biddle & Leuschner, 2015;Biddle et al, 2017;Leuschner, 2018) or gender bias denial (Leuschner & Fernández Pinto, 2021). James et al and Fryer do not bluntly deny that racism is widespread among police officers.…”
Section: The Inductive Risk Account Of Epistemically Detrimental Diss...mentioning
confidence: 74%
See 4 more Smart Citations
“…In sum, conditions 1 and 2 of the IndRA hold for the given case, but conditions 3 and 4 only partially. This indicates that the case differs from cases of epistemically detrimental dissent we have investigated more recently, such as denial of anthropogenic climate change (Biddle & Leuschner, 2015;Biddle et al, 2017;Leuschner, 2018) or gender bias denial (Leuschner & Fernández Pinto, 2021). James et al and Fryer do not bluntly deny that racism is widespread among police officers.…”
Section: The Inductive Risk Account Of Epistemically Detrimental Diss...mentioning
confidence: 74%
“…Beyond climate change, the IndRA conditions have also proven useful in identifying denialist research as epistemically detrimental in cases of research on social biases. Through an examination of recent studies denying the existence of gender bias in the academy (Ceci & Williams, 2011;Ceci et al, 2014;Williams & Ceci, 2015), we have shown that these investigations meet the four IndRA conditions and, therefore, are prone to producing similarly problematic consequences as in the case of climate change denialism (Leuschner & Fernández Pinto, 2021). They contribute to both widely-shared sexism in society and a social atmosphere that is hostile to science, as scholars investigating gender bias have been attacked (cf.…”
Section: The Inductive Risk Account Of Epistemically Detrimental Diss...mentioning
confidence: 86%
See 3 more Smart Citations